Sexual dysfunction caused not by organic disorders or somatic diseases. Dyspareunia and climacterium - Jarząbek-Bielecka, Grażyna (Menopause Review/Przegląd Menopauzalny, 2012)
Dyspareunia is defined as tenderness felt during a sexual intercourse without coexisting shrinkage of the vulva and vagina. It is a common sexual disorder in women, which is sometimes caused by hypoestrogenism connected with climacterium.